2009
DOI: 10.1111/j.1365-2109.2009.02240.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salinity on survival, growth, oxygen consumption and ammonia-N excretion of juvenile whiteleg shrimp,Litopenaeus vannamei

Abstract: In this study, we tested the lower salinity tolerance of juvenile shrimps (Litopenaeus vannamei) at a relatively low temperature (20 1C). In the ¢rst of two laboratory experiments, we ¢rst abruptly transferred shrimps (6.91 AE 0.05 g wet weight, mean AE SE) from the rearing salinity (35000 mg L À 1 ) to salinities of 5000, 15000, 25000, 35000 (control) and 40 000 mg L À 1 at 20 1C. The survival of L. vannamei juvenile was not a¡ected by salinities from 15000 to 40 000 mg L À 1 during the 96-h exposure periods.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 40 publications
1
23
0
3
Order By: Relevance
“…In another study, the growth rate of L. vannamei at 10 or 28 psu was also significantly higher than at 2 psu, but no growth difference was between 10 and 28 psu (Walker et al 2009 final weight was obtained at 5 and 15 psu, which significantly differed from those of shrimp at the salinity >25 psu, there was no significant difference between the final weights at 5 and 15 psu possibly due to short experimental duration (Bray et al 1994). Similarly, when shrimp were acclimatized to different salinities (5,15,25,35 or 40 psu), the survival was significantly lower at 5 psu than at other salinities, but the final wet weight was significantly higher than those at salinities exceeding 5 psu after 30 days (Zhang et al 2009). As the maintenance of internal ionic homeostasis, normal cellular function and other physiological processes in aquatic animals requires more energy, further more energy may require for osmoregulation at low salinity, leading to less energy for shrimp growth (Li et al 2008a).…”
Section: Physiological Response Of Litopenaeus Vannamei To Low Salinitymentioning
confidence: 78%
See 3 more Smart Citations
“…In another study, the growth rate of L. vannamei at 10 or 28 psu was also significantly higher than at 2 psu, but no growth difference was between 10 and 28 psu (Walker et al 2009 final weight was obtained at 5 and 15 psu, which significantly differed from those of shrimp at the salinity >25 psu, there was no significant difference between the final weights at 5 and 15 psu possibly due to short experimental duration (Bray et al 1994). Similarly, when shrimp were acclimatized to different salinities (5,15,25,35 or 40 psu), the survival was significantly lower at 5 psu than at other salinities, but the final wet weight was significantly higher than those at salinities exceeding 5 psu after 30 days (Zhang et al 2009). As the maintenance of internal ionic homeostasis, normal cellular function and other physiological processes in aquatic animals requires more energy, further more energy may require for osmoregulation at low salinity, leading to less energy for shrimp growth (Li et al 2008a).…”
Section: Physiological Response Of Litopenaeus Vannamei To Low Salinitymentioning
confidence: 78%
“…Similarly, when shrimp were acclimatized to different salinities (5, 15, 25, 35 or 40 psu), the survival was significantly lower at 5 psu than at other salinities, but the final wet weight was significantly higher than those at salinities exceeding 5 psu after 30 days (Zhang et al . ).…”
Section: Physiological Response Of Litopenaeus Vannamei To Low Salinitymentioning
confidence: 97%
See 2 more Smart Citations
“…Although shrimp are well adapted to cope with environmental changes, such as salinity, temperature, dissolved oxygen and pH changes (Brito, Chimal, & Rosas, ; Castille & Lawrence, ; Chen & Lai, ; Rosas et al. ; Spaargaren, Richard, & Ceccaldi, ; Zhang, Zhang, Li, & Gao, ), these changes are still stressful for the shrimp, and radicals generated from acute stress may result in oxidative stress or even mortality (Le Moullac & Haffner, ; Liu, Wang, Wang, Wang, & Sun, ; Wang & Chen, ). Moreover, previous studies reported that changes in salinity might be noxious to L. vannamei and olive flounder due to enhancement of reactive oxygen species (ROS) generation, inducing oxidative stress (Choi, An, & An, ; Liu et al., ).…”
Section: Introductionmentioning
confidence: 99%